2020
DOI: 10.3389/fimmu.2020.00287
|View full text |Cite
|
Sign up to set email alerts
|

Role of T Cells in Chikungunya Virus Infection and Utilizing Their Potential in Anti-Viral Immunity

Abstract: Chikungunya virus (CHIKV) is an arthropod-borne alphavirus that causes hallmark debilitating polyarthralgia, fever, and rash in patients. T cell-mediated immunity, especially CD4 + T cells, are known to participate in the pathogenic role of CHIKV immunopathology. The other T cell subsets, notably CD8 + , NKT, and gamma-delta (γδ) T cells, can also contribute to protective immunity, but their effect is not actuated during the natural course of infection. This review serves to consolidate and discuss the multifa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Although the role of T cells in CHIKV infection is still not fully understood, they most likely contribute to the protection against infection, since CHIKV is an intracellular pathogen. 29 Interestingly, some mice had only low IgG antibody titers but high T cell responses, and no correlation between antibody titers and T cell responses was found. Despite the induction of CHIKV-specific IgG antibodies, these were mainly non-neutralizing in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of T cells in CHIKV infection is still not fully understood, they most likely contribute to the protection against infection, since CHIKV is an intracellular pathogen. 29 Interestingly, some mice had only low IgG antibody titers but high T cell responses, and no correlation between antibody titers and T cell responses was found. Despite the induction of CHIKV-specific IgG antibodies, these were mainly non-neutralizing in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, vaccination with CHIKV-specific CD8 + T cell antigens protected mice from footpad swelling and reduced inflammation following wild-type CHIKV infection via the footpad [37]. In contrast, CHIKV-specific CD4 + T cells play a pathogenic role by induction of joint swelling without any effect on control of virus replication and dissemination [3,38]. In addition, one group reported that CD4 + T cells are nonessential for host protection following vaccination [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is transmitted by Aedes mosquitoes and causes chikungunya fever, which is often accompanied by severe, debilitating and chronic arthralgia [1]. The virus was initially associated with human disease in the 1950s in Tanzania and has reemerged over the last decade to cause epidemics in Africa, Asia, Europe, and the Americas [2,3]. Human vaccines are currently not available for CHIKV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these identified genes ( Cxcr6 , Crem , Clec7A , Fpr-rs3 and Nfil3 ) have known involvement with T cells leading to the hypothesis that T cell regulation may be an important mechanism of action of PPS. This is interesting as T cell-mediated immunity is known to contribute to the immunopathogenicity of CHIKV [ 70 , 71 ]. Furthermore, some of these molecules like IL-1β, HDAC5 and OLR1 (LOX-1) have already been flagged as potential therapeutic targets for RA [ 72 74 ] strengthening their importance in arthropathies.…”
Section: Discussionmentioning
confidence: 99%